Relationship between heart failure and central serous chorioretinopathy: A cohort study in Taiwan. Issue 12 (December 2019) - Huang, Ke-Hao; Chen, Yi-Hao; Lee, Lung-Chi; Tai, Ming-Cheng; Chung, Chi-Hsiang; Chen, Jiann-Torng; Liang, Chang-Min; Chien, Wu-Chien; Chen, Ching-Long
Abstract : Background: Both central serous chorioretinopathy (CSCR) and heart failure (HF) are disorders with a complex pathogenesis, whereas the two diseases might share similar pathogenesis. This study aimed to evaluate whether patients with HF are exposed to potential risk of CSCR by using the National Health Insurance Research Database (NHIRD). Methods: Data were collected from the NHIRD over a 14-year period. Variables were analyzed with the Pearson chi-square test and Fisher's exact test. The risk factors for disease development were examined by adjusted hazard ratio (aHR). Kaplan–Meier analysis was performed to compare the cumulative incidence of CSCR. Results: A total of 24 426 patients with HF were enrolled in the study cohort, and there were 24 426 patients without HF in the control cohort. The incidence rate of CSCR was higher in the study cohort than in the control cohort (aHR = 4.572, p < 0.001). CSCR occurred more commonly in males than in females. The overall incidence of CSCR was 30.07 per 100 000 person-years in the study cohort and 23.06 per 100 000 person-years in the control cohort. Besides, subgroup analysis revealed that no matter in gender or age group, HF patients were in an increased risk of CSCR diagnosis (male/female, aHR = 3.268/7.701; 20-59 years/≥60 years, aHR = 3.405/5.501, p < 0.001). Conclusion: HF is a significant indicator for CSCR. Patients with HF should stay alert for potential disorder of visual impairment. Further prospective studies to investigate the relationship between HF and CSCR could provide more information.